1988
DOI: 10.21236/ada195751
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Exploration of the Use of a Warfare Simulation Model to Examine the Military Value of Training

Abstract: The resul tso IDA work art also conveyed by briefings and Informai memoranda to sponsors and othes deisrulgted bit the sponsors, when appropriate. The work ruportust in this doocoroet was conducted under contract MDA 903 84 C 0031 for the Department of Defense TMe publicat ion of this IDA document does not Indicate endorsement by the Departmnt at Bulows, nor should the contents be construed as reflecting the Official postm" at thef agency. Ii Ws paper hee been reviewed by IDA to assure that It meets high stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…At any rate, the samples are too small to suggest more than the general order of magnitude of the change in the two cases. Figure 10 reproduces the results of IDA Paper P-2094 (Deitchman, 1988) that show the impact of improvement in armored force performance on the outcome of the war played in the TACWAR modeL It can be seen that an improvement of 20-35 percent would _ have little impact on the ultimate result. To achieve the necessary factor of 2 or more improvement in armor capability, one would have to shift from the M-60 series to the M-1 series of tanks; other analytic studies show that much improvement or more in moving from the older to the newer tank (a quantitative experimental comparison of unit * •performance with the two tanks on terms comparable with those in this review has not yet been found, and may not exist).…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…At any rate, the samples are too small to suggest more than the general order of magnitude of the change in the two cases. Figure 10 reproduces the results of IDA Paper P-2094 (Deitchman, 1988) that show the impact of improvement in armored force performance on the outcome of the war played in the TACWAR modeL It can be seen that an improvement of 20-35 percent would _ have little impact on the ultimate result. To achieve the necessary factor of 2 or more improvement in armor capability, one would have to shift from the M-60 series to the M-1 series of tanks; other analytic studies show that much improvement or more in moving from the older to the newer tank (a quantitative experimental comparison of unit * •performance with the two tanks on terms comparable with those in this review has not yet been found, and may not exist).…”
mentioning
confidence: 71%
“…The results of this analysis show that training yields quantifiable improvements in performance, in the areas of warfare examined. The magnitude is sizeable, especially in the case of tactical bombing, but does not appear to offer a decisive change in the military balance as the latter was assessed in the earlier work (Deitchman, 1988).…”
mentioning
confidence: 88%
See 3 more Smart Citations